Inappropriate disabling of an ICD noise‐detection algorithm in pacemaker‐dependent patients. Issue 4 (12th December 2018) - Welte, Nicolas; Gang, Eli S.; Swerdlow, Charles D.; Strik, Marc; Bordachar, Pierre; Ploux, Sylvain
Abstract: SecureSense is an implantable cardioverter defibrillator algorithm that differentiates lead‐related oversensing from ventricular tachycardia/ventricular fibrillation by continuous comparison between the near‐field (NF) and the far‐field (FF) electrogram. If lead noise is identified, inappropriate therapy is withheld. Undersensing on the FF channel could result in inappropriate inhibition of life‐saving therapy. Thus, the device automatically switches SecureSense to passive mode if undersensing on the FF channel is suspected. We report here the first cases of inappropriate automatic SecureSense deactivation due to misdiagnosed FF undersensing in pacemaker‐dependent patients. Physicians should be aware that SecureSense does not withhold an inappropriate therapy for sustained oversensing in pacemaker‐dependent patients.